Hubungan Dana Desa dengan Pembangunan Ekonomi Desa: Studi tingkat Desa di Indonesia: Studi Tingkat Desa di Indonesia - Yusuf, Mohamad; Khoirunurrofik, Khoirunurrofik (Jurnal Bina Praja, 2022)
The Village Fund Program is a manifestation of fiscal decentralization in Indonesia, which is intended to support equitable development and increase community welfare. The village government has the authority to plan the use of the Village Fund and to spend it concerning regulations from the central government. The use of the Village Fund needs to be evaluated to determine whether the funds have been spent properly and support the village's economic development. This study aims to identify Village Fund program activities that can affect village economic development and determine regional priorities in utilizing Village Funds for village development in the economic field. The analysis was conducted using a qualitative approach by mapping and tagging Village Fund expenditures. The mapping and tagging aim to ensure that Village Fund spending follows the mandate and to know the composition of the share of economic spending in each region. The results showed that: (1) the utilization of the Village Fund was following the applicable priority guidelines for the use of the Village Fund; (2) the share of economic spending in the eastern part of Indonesia is lower than in other regions, but the trend is constantly rising, while the share of economic spending in the islands of Java and Bali shows a higher number. Based on the research results, this study suggests that villages in disadvantaged areas prioritize Village Fund spending for infrastructure improvement and regional openness to increase village progress or independence.